To See and be Seen—Perceived Ethics and Acceptability of Pervasive Augmented Reality - Holger Regenbrecht; Alistair Knott; Jennifer Ferreira; Nadia Pantidi (IEEE Access, 2024)
Augmented reality (AR) glasses are likely to become omnipresent, providing a continuous and ubiquitous experience of computer-mediated reality. This new Pervasive AR will lead to perceptual, acceptance, and ethical issues which are increasingly discussed in the literature. However, given such Pervasive AR prototypes are currently not commercially available, little is known about potential end-users’ input into this discussion. To address this, we developed a Pervasive AR (PAR) prototype serving as a technology probe and conducted an empirical study in a semi-public space involving 54 participants. We collected data from focus groups, questionnaires, and observations of users and bystanders. Extending concerns with existing technology, like smartphones and augmented reality, PAR exposes privacy and security breaches with its unprompted, all-seeing capability, has a higher potential to cause societal fractures and divisions, and raises new questions on information transparency and trust with significant implications for the design of future PAR systems.